FACTORS DETERMINING MARKETING PERFORMANCE OF FASHION SMEs IN JAKARTA: THE PERSPECTIVE OF MARKETING SKILLS, CRM, AND COMPETITION INTENSITY: FAKTOR PENENTU KINERJA PEMASARAN UMKM FASHION DI JAKARTA: PERSPEKTIF KETERAMPILAN PEMASARAN, CRM, DAN INTENSITAS PERSAINGAN - Rifai Kukuh Widiyanto; Jubaedah Jubaedah; Alfatih Sikki Manggabarani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study analyzes the Marketing Performance of the Fashion MSME Industry in Jakarta. The purpose of this study is to examine the influence of marketing skills and customer relationship management on marketing performance through competitive intensity. This study is quantitative by distributing questionnaires to 240 MSME actors. Using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the Smart-PLS 4.0 program. The results of the data analysis show that: (1) Marketing Skills have a significant effect on Marketing Performance through Competitive Intensity in the Fashion Industry in Jakarta. (2) while Customer relationship management has a direct effect on Marketing Performance without considering the Intensity of Competition in the Fashion Industry in Jakarta